Digest. International Electron Devices Meeting,
DOI: 10.1109/iedm.2002.1175826
|View full text |Cite
|
Sign up to set email alerts
|

25 nm CMOS Omega FETs

Abstract: Low leakage and low active-power 25 nm gate length C-MOSFETs are demonstrated for the first time with a newly proposed Omega-(0) shaped slruchue, at a conservative 17-19 A gate oxide thickness, and with excellent hot carrier immunity. For 1 volt operation, the transistors give drive currents of 1440 pNpm and 780 pA/pm with off state leakage currents of 8 n N p and 0.4 nNpm for N-FET and P-FET, respectively. A low voltage version achieves, at 0.7 V, drive currents of 1300 p A / p for N-FET and 550 pNpm for P-FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…It can be easily obtained by a slight overetching of the buried oxide during the Si island patterning. The gate extension improves the control of the channel by the gate and thereby lowers the role of short-channel effects [16,18,[114][115][116]. As can be seen from Fig.…”
Section: An Advanced Approach For Mosfet Downsizing In Nanometer Regionmentioning
confidence: 85%
“…It can be easily obtained by a slight overetching of the buried oxide during the Si island patterning. The gate extension improves the control of the channel by the gate and thereby lowers the role of short-channel effects [16,18,[114][115][116]. As can be seen from Fig.…”
Section: An Advanced Approach For Mosfet Downsizing In Nanometer Regionmentioning
confidence: 85%
“…In 1999, Huang et al [8] demonstrated the first FinFET with a gate length L G of sub-50 nm and a fin width of 15− 30 nm. Following that, leading research groups and foundries like IBM [11] , STMicroelectronics [15] , Intel [5,10] , TSMC [16,27] , Samsung [17] . IME [18] , etc.…”
Section: Process Development Of Si Multi-gate Transistors 21 a Histor...mentioning
confidence: 99%
“…(a-f) Schematics of MuGFETs with different gate geometries: (a) IMEC's gate-all-around (GAA) MOSFET [14] , (b) the world-first FinFET [8] , (c) IBM's double-gate (DG) FinFET [11] , (d) STMicroelectronics's GAA MOSFET [15] , (e) Intel's tri-gate FinFET [10] , (f) TSMC's nanowire FinFET [16] . (g-i) TEM images showing the cross-sectional view of fins/nanowires from early works: (g) IBM's DG FinFET [11] , (h) Intel's tri-gate FinFET [10] , (i) Samsung's nanowire MOSFET [17] , (j) IME's nanowire GAA MOSFET [18] , (k) TSMC's FinFET [27] , (l) STMicroelectronics's GAA MOSFET [28] . ferent process technology, namely, bulk planar FETs, fully-depleted SOI (FDSOI) FETs, and FinFETs [29] .…”
Section: Process Development Of Si Multi-gate Transistors 21 a Histor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Source-to-drain quantum tunnelling [7]- [9] or variability [10]- [12] is much more pronounced and deteriorate the I ON /I OFF ratio in current ultrascaled devices. To overcome this problem, a variety of new architectures, including ultrathin silicon-on-insulator (SOI) [13]- [15], double gate [13], [16], FinFETs [17], [18], trigate [19], -gate [20], junctionless (JL) [21], and gate all-around nanowire FETs [22], have therefore been developed to improve the electrostatic control of the conducting channel. In those architectures, the surface surrounded by the gate is increased in relation to the channel volume, improving the electrostatic control.…”
Section: Impact Of Randomly Distributed Dopants Onmentioning
confidence: 99%